Differential Expression of Myogenic Regulatory Factor Genes in the Skeletal Muscles of Tambaqui Colossoma macropomum (Cuvier 1818) from Amazonian Black and Clear Water - Alves-Costa, F. A.; Barbosa, C. M. [UNESP]; Aguiar, R. C. M. [UNESP]; Mareco, E. A. [UNESP]; Dal-Pai-Silva, M. [UNESP] (Hindawi Publishing Corporation, 2013)
Hypothesizing that the Amazonian water system differences would affect the expression of muscle growth-related genes in juvenile tambaqui Colossoma macropomum (Cuvier 1818), this study aimed to analyze the morphometric data and expression of myogenic regulatory factors (MRFs) in the white and red muscle from tambaqui obtained from clear and black Amazonian water systems. All of the MRF transcript levels (myod, myf5, myogenin, and mrf4) were significantly lower in the red muscle from black water fish in comparison to clear water fish. However, in white muscle, only the myod transcript level was significantly decreased in the black water tambaqui. The changes in MRFs gene expression in muscle fibers of tambaqui from black water system provide relevant information about the environmental influence as that of water systems on gene expression of muscle growth related genes in the C. macropomum. Our results showed that the physical and chemical water characteristics change the expression of genes that promote muscle growth, and these results may be also widely applicable to future projects that aim to enhance muscle growth in fish that are of substantial interest to the aquaculture.